2001
DOI: 10.1093/clipsy/8.4.463
|View full text |Cite
|
Sign up to set email alerts
|

ADHD Combined Type and ADHD Predominantly Inattentive Type Are Distinct and Unrelated Disorders

Abstract: We comprehensively reviewed research assessing differences in attention-deficit hyperactivity disorder (ADHD) subtypes to examine the possibility that ADHD/ combined type (ADHD/C) and ADHD/predominantly inattentive type (ADHD/I) are distinct and unrelated disorders. Differences among subtypes were examined along dimensions identified as being important in documenting the distinctiveness of two disorders. These include essential and associated features, demographics, measures of cognitive and neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
250
9
22

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(299 citation statements)
references
References 42 publications
(113 reference statements)
18
250
9
22
Order By: Relevance
“…In fact, in both the childhood-diagnosed and adolescent-diagnosed analyses, these "type" differences were never significant except for one instance for the adolescent-diagnosed girls, even though power calculations reveal that, given our follow-up sample sizes, we have statistical power of nearly .6 to detect effects of medium size (see Faul & Erfelder, 1992). Despite contentions that the inattentive type of ADHD is a separate, qualitatively distinct variant of this disorder, particularly with respect to cognitive performance (Milich et al, 2001), we found no such evidence, at least with respect to the variables in our battery. Whether other cognitive measures would yield such effects must await additional research.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In fact, in both the childhood-diagnosed and adolescent-diagnosed analyses, these "type" differences were never significant except for one instance for the adolescent-diagnosed girls, even though power calculations reveal that, given our follow-up sample sizes, we have statistical power of nearly .6 to detect effects of medium size (see Faul & Erfelder, 1992). Despite contentions that the inattentive type of ADHD is a separate, qualitatively distinct variant of this disorder, particularly with respect to cognitive performance (Milich et al, 2001), we found no such evidence, at least with respect to the variables in our battery. Whether other cognitive measures would yield such effects must await additional research.…”
Section: Discussioncontrasting
confidence: 99%
“…Given claims that this variant of ADHD represents a qualitatively distinct condition (Milich, Balentine, & Lynam, 2001), such followup is a priority, particularly with respect to objective outcomes, which are likely to be less biased than reports from adult informants.…”
mentioning
confidence: 99%
“…In general, the incidence of ADHD did not seem related to P50 potential amplitude. Interestingly, our study sample had a higher representation of females with ADHD (24% in females and 14% in males), consistent with others who have found a similar male to female ratio for ADHD in Ex-Preterm children compared to male predominance of ADHD in the general population (Milich et al 2001).…”
Section: Adhdsupporting
confidence: 92%
“…It is possible that the predominantly inattentive subtype exhibits problems with inattention that are more severe than those experienced by children with the combined subtype in their impact on academic learning. On the other hand, the present findings raise the possibility that younger children who meet criteria for the inattentive type have qualitatively different problems (Milich, Balentine, & Lynam, 2001). For example, it is possible that the inattentive group has serious deficits in academic skill learning that lead to their symptoms of inattention.…”
Section: Discussionmentioning
confidence: 56%